A silent sin?: An investigation into the provision of community based non-governmental support services for male victims of sexual violence in South Africa - Petrovic, Vanja (Institute of Criminology, 2017)
This minor dissertation examines the status quo of services provision by community based victim support services for male victims of sexual violence in South Africa. Given the scale of gender-based violence in South Africa it comes as no surprise that research and debates around sexual violence have predominately focused on women as victims and men as perpetrators. In this minor dissertation the neglect of men as potential and actual victims of sexual violence are problematized. In the discussion I explore the issues at stake, assess the status of male victims and investigate the kinds of services available to sexually violated men in the country. The research methods utilised include the following: a review of the international and national academic literature regarding male sexual victimisation; a review of relevant legislation and policies in South Africa; a review of media coverage on male rape and male sexual victimisation; content analysis of community based service providers' web sites and interviews with service providers. Despite the tendency to use gender neutral language in some official discourses (legislation, policy documents or service providers' official presentations and communications) to stipulate that everyone can be a victim of sexual violence irrespective of gender, male victims remain hidden from view. The interviews, however, showed a sound acknowledgement within the service providers that male sexual violence is a problem in the country that has to be taken seriously and acted upon. Services are available to men, but the design, delivery of services and training of professionals working with male victims differ from organisation to organisation. The visibility of those services, however, remains a question. By way of conclusion a list of recommendations for more effective service delivery to male victims of sexual violence is provided, which highlight the need for more 1) advocacy and awareness raising, 2) more evidence-based research, 3) funding), 4) training of professionals working with survivors of sexual violence and 5) cooperation between stakeholders.